Navigating Divine Will: A Qur’anic Theological Analysis of Abraham’s Sacrifice and Noah’s Ark Narratives - Adrian Mafatihullah Karim; Jarman Arroisi; Amir Sahidin; Nur Hadi Ihsan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Contemporary spiritual, social, and ecological crises highlight the need for a theological framework that helps individuals navigate uncertainty. This study examines the narratives of Prophet Abraham’s sacrifice and Prophet Noah’s Ark through the concept of unknown navigation, defined as a theological condition in which believers act upon divine guidance despite limited knowledge of its outcomes and wisdom. Unlike previous studies that treat these narratives separately as accounts of obedience and salvation, this article proposes unknown navigation as a theological lens for understanding prophetic responses to existential uncertainty. This qualitative study employs thematic Qur’anic exegesis (tafsīr mawḍū‘ī) and historical-textual analysis of Qur’anic passages concerning Abraham and Noah. The analysis focuses on obedience, trials of faith, divine guidance, and spiritual salvation. The findings reveal a common theological pattern: obedience to revelation precedes certainty about outcomes. Abraham accepted the command to sacrifice his son without knowing its resolution, while Noah built the Ark without knowing when or how salvation would occur. These narratives demonstrate that unknown navigation represents a spiritual model grounded in faith, surrender, and trust in Allah. The study contributes to contemporary Islamic theology by offering a conceptual framework for understanding divine guidance and human agency amid modern crises of identity, morality, and spirituality.